Natural Intrinsic Geometrical Symmetries - Stefan Haesen; Leopold Verstraelen (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
A proposal is made for what could well be the most natural symmetrical Riemannian spaces which are homogeneous but not isotropic, i.e. of what could well be the most natural class of symmetrical spaces beyond the spaces of constant Riemannian curvature, that is, beyond the spaces which are homogeneous and isotropic, or, still, the spaces which satisfy the axiom of free mobility.